2020
DOI: 10.1161/circep.119.007726
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lead Adherence Using Intravascular Ultrasound to Assess Difficulty of Transvenous Lead Extraction

Abstract: Background - Clinical factors associated with development of intravascular lead adherence (ILA) are unreliable predictors. Because vascular injury in the superior vena cava - right atrium (SVC-RA) during transvenous lead extraction (TLE) is more likely to occur in segments with higher degrees of ILA, reliable and accurate assessment of ILA is warranted. We hypothesized that intravascular ultrasound (IVUS) could accurately visualize and quantify ILA and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…It is important to note that presently there is an increasing trend to utilize intraprocedural echocardiographic imaging not only for detection of procedural complications but also for risk stratification during TLE procedures. Several studies evaluated the utility of intraprocedural ICE and intravascular ultrasound for real‐time visualization of the intravascular lead course and adherence during TLE procedures 5,11 . However, while some high‐risk features on those imaging modalities were shown to help identify a subset of patients whose extractions might be more difficult and complex, correlation with procedural success and safety has been lacking 5,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that presently there is an increasing trend to utilize intraprocedural echocardiographic imaging not only for detection of procedural complications but also for risk stratification during TLE procedures. Several studies evaluated the utility of intraprocedural ICE and intravascular ultrasound for real‐time visualization of the intravascular lead course and adherence during TLE procedures 5,11 . However, while some high‐risk features on those imaging modalities were shown to help identify a subset of patients whose extractions might be more difficult and complex, correlation with procedural success and safety has been lacking 5,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated the utility of intraprocedural ICE and intravascular ultrasound for real-time visualization of the intravascular lead course and adherence during TLE procedures. 5,11 However, while some high-risk features on those imaging modalities were shown to help identify a subset of patients whose extractions might be more difficult and complex, correlation with procedural success and safety has been lacking. 5,11 This is consistent with the results of our study, whereby the lack of echocardiographic information regarding lead adherence did not appear to adversely influence the TLE procedural outcome, given the high success and low complication rates in our cohort.…”
Section: Fluoroscopy Versus Echocardiographymentioning
confidence: 99%
“…3 Other studies utilizing IVUS and ICE have also reported an association between lead adherence and increased TLE complexity. 4,5 Interestingly, Beaser et al reported that the finding of minimal adhesions by intravascular ultrasound were associated with lower complexity during TLE even in the setting of other clinical factors which typically predict higher complexity such as lead dwell time, presence of multiple leads and the presence of an SVC coil. 4 In fact, even adhesions in the pocket have been associated with increased TLE complexity and the need for a higher number of extraction tools.…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…4,5 Interestingly, Beaser et al reported that the finding of minimal adhesions by intravascular ultrasound were associated with lower complexity during TLE even in the setting of other clinical factors which typically predict higher complexity such as lead dwell time, presence of multiple leads and the presence of an SVC coil. 4 In fact, even adhesions in the pocket have been associated with increased TLE complexity and the need for a higher number of extraction tools. 8 While Aboelhassan et al found an association between lead-venous adherence and procedure complexity, there was no such association in patients with venous occlusion.…”
Section: Findings and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation